Oscillating Aquaporin Phosphorylation and 14-3-3 Proteins Mediate the Circadian Regulation of Leaf Hydraulics. Issue 2 (23rd January 2019) - Prado, Karine; Cotelle, Valérie; Li, Guowei; Bellati, Jorge; Tang, Ning; Tournaire-Roux, Colette; Martinière, Alexandre; Santoni, Véronique; Maurel, Christophe
Abstract : A mechanism is established that tunes the hydraulics of leaf tissues to synchronize water supply with day and night cycles, thereby optimizing plant growth. Abstract: The circadian clock regulates plant tissue hydraulics to synchronize water supply with environmental cycles and thereby optimize growth. The circadian fluctuations in aquaporin transcript abundance suggest that aquaporin water channels play a role in these processes. Here, we show that hydraulic conductivity ( K ros ) of Arabidopsis ( Arabidopsis thaliana ) rosettes displays a genuine circadian rhythmicity with a peak around midday. Combined immunological and proteomic approaches revealed that phosphorylation at two C-terminal sites (Ser280, Ser283) of PLASMA MEMBRANE INTRINSIC PROTEIN 2;1 ( At PIP2;1), a major plasma membrane aquaporin in rosettes, shows circadian oscillations and is correlated with K ros . Transgenic expression of phosphodeficient and phosphomimetic forms of this aquaporin indicated that At PIP2;1 phosphorylation is necessary but not sufficient for K ros regulation. We investigated the supporting role of 14-3-3 proteins, which are known to interact with and regulate phosphorylated proteins. Individual knockout plants for five 14-3-3 protein isoforms expressed in rosettes lacked circadian activation of K ros . Two of these [GRF4 (14-3-3Phi); GRF10 (14-3-3Epsilon)] showed direct interactions with At PIP2;1 in the plant and upon coexpression in Xenopus laevis oocytes and activated At PIP2;1, preferentially when the latter was phosphorylated at its two C-terminal sites. We propose that this regulatory mechanism assists in the activation of phosphorylated At PIP2;1 during circadian regulation of K ros .